2019
DOI: 10.3802/jgo.2019.30.e85
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of neutrophil-to-lymphocyte ratio in early-stage ovarian clear-cell carcinoma

Abstract: ObjectivesThere is increasing evidence that systemic inflammatory response (SIR) markers are prognostic factors for various types of cancers. This is the first study to evaluate the usefulness of SIR markers for the prognosis of early-stage ovarian clear-cell carcinoma (OCCC).MethodsWe retrospectively investigated 83 patients diagnosed with stage I–II OCCC who underwent surgery between 2005 and 2017. Initially, receiver operating characteristic curve analysis for overall survival (OS) was used to determine opt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
27
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 23 publications
3
27
0
2
Order By: Relevance
“…Four studies on the effectiveness of SIR markers in OCCC patients have been reported in the last ve years, as shown in Table 4. Concerning NLR, most of the previous reports suggested that NLR was a prognostic indicator for PFS and/or OS [13,19,20] . There are some con icting results regarding PLR.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Four studies on the effectiveness of SIR markers in OCCC patients have been reported in the last ve years, as shown in Table 4. Concerning NLR, most of the previous reports suggested that NLR was a prognostic indicator for PFS and/or OS [13,19,20] . There are some con icting results regarding PLR.…”
Section: Discussionmentioning
confidence: 99%
“…Summary of studies examining SIR as prognostic factors in OCCC patients. Kim 2016 [19] Zhang 2017 [20] Kwon 2018 [12] Yoshida 2019 [13] The present study…”
Section: Authors' Contributionsmentioning
confidence: 94%
See 1 more Smart Citation
“…There are four studies on the effectiveness of SIR markers in OCCC patients in the last five years, as shown in Table 4. Concerning NLR, most of the previous reports suggested that NLR was a prognostic indicator for PFS and/or OS [13,19,20] . There are some conflicting results regarding PLR, with one study suggesting that high PLR was associated with unfavorable outcomes, advanced stage, resistance to primary treatment and decreased survival [19] , while others did not.…”
Section: Discussionmentioning
confidence: 99%
“…The plasma D-dimer level, which significantly elevates in patients with OCCC, was associated with the incidence of deep venous thrombosis [7] as well as clinical progression and poor prognosis in malignancies including ovarian cancer [8,9] . Plenty of studies have shown that elevated NLR is linked to poor prognosis among patients with solid tumors including gynecologic cancers [10,11] , and markers of systemic inflammatory response could provide useful prognostic information of overall survival in patients with OCCC [12,13] .…”
Section: Introductionmentioning
confidence: 99%